Magnesium for Florida Turfgrasses - Travis W. Shaddox (EDIS)
Soluble magnesium (Mg) is often applied to turfgrasses in both granular and foliar forms, and is therefore essential to understanding the function of Mg in the plant, the dynamics of Mg in the soil, and the forms of Mg fertilizers. This 3-page document discusses the function and forms of magnesium in turfgrasses. Written by T. W. Shaddox and published by the UF/IFAS Environmental Horticulture Department, March 2018. http://edis.ifas.ufl.edu/ep555